Knowledge Sharing In A Data Warehousing Project: An Investigation Into The Dimensions Of What, When, And How Knowledge Is Shared - Nemani, Rao (Journal of Knowledge Management Practice, 2012)
The knowledge sharing in a data warehouse (DW) project is important for managing knowledge for any organization and is critical for its survival. The purpose of this study was to examine the practices of knowledge sharing in terms of what, when, and how knowledge is shared in a DW project. The practices of knowledge sharing in a DW project through the dimensions of what, when, and how knowledge is shared was explored in a DW project. The study design was quantitative and used a web-enabled survey to collect data from 110 DW professionals using a single stage, cross-sectional approach. The study involved what, when and how knowledge is shared in a DW project from the participant’s perspective as knowledge providers as well as knowledge receivers. It is expected that the research finding will provide DW managers with an insight into what, when, and how to best share knowledge for a successful DW projects.